Host and Microbial Factors in Regulation of T Cells in the Intestine - Kim, Chang H. (Frontiers in Immunology, 2013)
The intestine is divided into specialized tissue areas that provide distinct microenvironments for T cells. Regulation of T cell responses in the gut has been a major focus of recent research activities in the field. T cells in the intestine are regulated by the interplay between host and microbial factors. In the small intestine, retinoic acid (RA) is a major tissue factor that plays important roles in regulation of immune responses. In the large intestine, the influence of RA diminishes, but that of commensal bacterial products increases. RA, gut microbiota, and inflammatory mediators co-regulate differentiation, distribution, and/or effector functions of T cells. Coordinated regulation of immune responses by these factors promotes well-balanced immunity and immune tolerance. Dysregulation of this process can increase infection and inflammatory diseases.